Consensus statement on the methodology of injury and illness surveillance in FINA (aquatic sports). Issue 10 (27th November 2015) - Mountjoy, M; Junge, A; Alonso, J M; Clarsen, B; Pluim, B M; Shrier, I; van den Hoogenband, C; Marks, S; Gerrard, D; Heyns, P; Kaneoka, K; Dijkstra, H P; et al.
Abstract : Background: Injury and illness surveillance in the aquatic disciplines has been conducted during the FINA World Championships and Olympic Games. The development of an aquatic-specific injury and illness surveillance system will improve the quality of the data collected and the development of preventive measures. Our ultimate objective is to enhance aquatic athlete health and performance. Objective: The objective was to refine the injury and illness surveillance protocols to develop aquatic-specific definitions of injury and illness; define aquatic-specific injury location and causation; better describe overuse injuries; regard pre-existing and recurrent injuries; more accurately define aquatic athlete exposures and develop a protocol to capture out-of-competition aquatic athlete health parameters. Methods: FINA compiled an Injury and Illness Surveillance Expert Working Group comprised of international experts to review the scientific literature in the field. A consensus meeting was convened to provide an opportunity for debate, following which recommendations were collated. Results: Aquatic-specific injury and illness surveillance protocols covering both the in-competition and out-of-competition time periods were developed. Definitions for all relevant variables were outlined, and documentation forms for athletes and for clinicians were proposed. Recommendations for the implementation of an injury and illness surveillance system for FINA are presented. Conclusion: The FINA consensus authors recommend ongoing in-competition and out-of-competition surveillance to determine injury and illness trends over time. The implementation of the definitions and methodology outlined in this paper will improve the accuracy and value of injury and illness surveillance, and provide important information for injury prevention.